Gluing of radiata pine veneer with ureaformaldehyde - Devlieger S., Francis; Rademacher R., José (Bosque (Valdivia), 1989)
The purpose of this work was to assess various methods of gluing radiata pine plywood with a wood moisture content above 10% using ureaformaldehyde. The following variables and levels were examined: temperature: 105° C and 120° C; wood moisture content: 10%, 15% and 20%, extender in the glue mixture: 0%, 20% and 30%. The quality of gluing was graded according to british standard BS 6566 class MR. A wetting agent (Teepol) was added in the proportion of 1% with respect to the total weight of the mixture with the objective of counteracting the effect of the resin. The analysis of the results indicated that the variables examined did not have a marked effect on shear stength. However, pressing temperature and percentage of extender had a notable influence on wood failure whereas the moisture content had little effect.